A METHODOLOGICAL FRAMEWORK FOR VOCAL RESONANCE TRAINING: INTEGRATING PHARYNGEAL VOICE PEDAGOGY AND MODERN ACOUSTICS - Peng , Chengqiu; Tee , Xiao Xi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Vocal resonance is the fundamental aspect of the quality of singing, projection, and richness of expression, but current training methods are still disjointed. Pedagogical approaches, e.g., the Eight Steps of Pharyngeal Voice Training offered by Lin Junqing, are valuable and practical, yet they are not always put into a systematic setup in an academic approach. Modern acoustic research, on the other hand, provides more elaborate explanations of resonance phenomena, such as formant tuning, singer formant and resonance tube phonation, but these results have not been applied to vocal pedagogy. This paper suggests a conceptual framework for vocal resonance training combining the traditional theoretical pharyngeal voice training with the modern theory of acoustics. The framework is conceptually a ten-step framework based on the literature synthesis and pedagogic analysis of the eight-step model presented by Lin, with each step characterised by its pedagogical goal, physiological process, anticipated outcome and scholarly support. This paper indicates that the suggested framework will help develop a more systematic perspective on resonance pedagogy and its applicability to performing arts research.